STRATEGIES FOR STRENGTHENING MODERATE ISLAMIC VALUES IN FORMAL EDUCATION AT PESANTREN DARUL MUSTHOFA - Syarifuddin, Ahmad; Badaruddin, Muhammad; Irawan, Muhammad Hendri; Aminudin S, Muh. Dzihab; Aprizal, Yobi; Sulkhi Aunillah, M. Zulfikar (Conciencia, 2025)
The growing prevalence of intolerance among younger generations presents a significant challenge for contemporary education, particularly within Islamic educational institutions. Islamic boarding schools (pesantren) hold a strategic position as agents of character formation, especially in cultivating moderation and tolerance through education grounded in moderate Islamic values. This study aims to examine the strategies employed to strengthen moderate Islamic values in formal education at Darul Musthofa Al Mahmudany Islamic Boarding School in Pesawaran, Lampung. Adopting a qualitative field research approach, the study involved seven purposively selected participants, including pesantren leaders, teachers (ustadz), senior students, alumni, and community leaders. Data were collected through observation, in-depth interviews, and document analysis, and were analyzed using the interactive model proposed by Miles and Huberman. The findings reveal that the pesantren systematically integrates moderate Islamic values into its curriculum, teaching practices, and the daily lives of students. These strategies encompass the integration of religious and general education curricula, the exemplary conduct of the kyai, the promotion of tolerance through religious discussions and social activities, as well as the utilization of digital media as a platform for moderate da’wah. Moreover, active engagement with the surrounding community further reinforces the internalization of wasathiyah values. Overall, the pesantren demonstrates a contextual and adaptive model of Islamic education that plays a significant role in shaping inclusive students with a strong sense of national identity.